Fractionation of Cellulose-Rich Products from an Empty Fruit Bunch (EFB) by Means of Steam Explosion Followed by Organosolv Treatment - Jae Hoon Lee; Muhammad Ajaz Ahmed; In-Gyu Choi; Joon Weon Choi (Applied Sciences, 2020)
In this study an empty fruit bunch (EFB) was subjected to a two-step pretreatment to defragment cellulose-rich fractions as well as lignin polymers from its cell walls. First pretreatment: acid-catalyzed steam explosion (ACSE) pretreatment of EFB was conducted under the temperature range of 180−220 °C and residence time of 5−20 min. The ACSE-treated EFB was further placed into the reactor containing 50% aq. ethanol and NaOH as a catalyst and heated at a temperature of 160 °C for 120 min for the second pretreatment: alkali-catalyzed organosolv treatment (ACO). The mass balance and properties of treated EFB were affected by the residence time. The lowest yield of a solid fraction was obtained when the residence time was kept at 15 min. Xylose drastically decreased, especially under the ACSE pretreatment. However, the crystallinity of cellulose increased by increasing the severity factor of the pretreatment and was 47.8% and 57% udner the most severe conditions. The organosolv lignin fractions also showed the presence of 14 major peaks via their pyrolysis-GC analysis. From here, it can be suggested that this kind of pretreatment can indeed be one potential option for lignocellulosic pretreatment.